Nazi characters in German propaganda and literature - Lorenz, Dagmar C. G. (2018)
Stereotypical characters that promoted the Nazi worldview were repurposed by antifascist authors in Weimar Germany, argues Dagmar C.G. Lorenz. This is the first book to trace Nazi characters through the German and Austrian literature. Until the defeat of the Third Reich, pro-Nazi literature was widely distributed. However, after the war, Nazi publications were suppressed or even banned, and new writers began to dominate the market alongside exile and resistance authors. The fact that Nazi figures remained consistent suggests that, rather than representing real people, they functioned as ideological signifiers. Recent literature and films set in the Nazi era show that "the Nazis", ambiguous characters with a sinister appeal, live on as an established trope in the cultural imagination